Goal projection in public places. (15th May 2015) - Naju Ahn, Janet; Oettingen, Gabriele; Gollwitzer, Peter M.
Abstract Three studies investigated the phenomenon of goal projection in everyday life considering three moderators: goal commitment, the perceived similarity of the target person, and goal attainment. Moviegoers' (Study 1) highly committed to see a particular movie projected this goal onto other movie patrons. Commuters (Study 2) highly committed to catch a certain train projected this goal onto other commuters, given that these commuters were perceived as similar. Shoppers (Study 3) projected buying a particular item when both their goal commitment and the perceived similarity of another shopper were high, and the goal was not yet attained. The results imply that goal projection is part of our everyday life and is fostered by high‐goal commitment, perceiving others as similar, and ongoing goal striving.